Structural, magnetic, and gas adsorption study of a series of partially fluorinated metal-organic frameworks (HF-MOFs) - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Inorganic Chemistry, 2011)
Four new partially fluorinated metal organic frameworks (HF-MOFs) have been synthesized under different solvothermal conditions (H2O or dimethylformamide (DMF)) from transition metal cations [Co2+ and Mn2+], 3-methyl pyridine (3-mepy) and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba), to determine the influence of reaction conditions on the formation of MOFs. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. HF-MOFs synthesized from H2O [Co-HFMOF-W, Co(liffiba)(3-mepy)(H2O) and Mn-HFMOF-W, Mn(hfbba)(3-mepy)(H2O)] contain three-dimensional connectivity whereas HF-MOFs synthesized from DmF Co-HFMOF-D, [Co-2(hfbba)(2)(3-mepy)(2)]center dot(DMF)(3) and Mn-HFMOE-D, [Mn-2(hfbba)(2)(3-mepy)]center dot(H2O) are two-dimensional in nature. Co-HFMOF-W and Mn-HFMOF-W are iso-structural polymeric materials. Thermal gravimetric analysis performed on as-synthesized HP-MOFs revealed that these compounds have high thermal stability (similar to 350 degrees C). The continuous decrease of the chi T product with decreasing T for Co-HFMOF-D and Co-HFMOF-W respectively indicates the presence of antiferromagnetic exchange interaction between two Co2+ (S = 3/2) metal centers within a duster.